The FTTdp technology option for the Australian National Broadband Network - Watkins, Craig; Lillingstone-Hall, Kelvin (Journal of Telecommunications and the Digital Economy, 2014)
Fibre to the Distribution Point (FTTdp) is a broadband access network technology that encompasses fibre to the street lead-in pit at the front fence, with an average copper lead-in length of 30m. FTTdp promises very high VDSL2 capability, with easy upgrading to G.fast or individual FTTP (Fibre to the Premises) on an on-demand basis. The network capability of FTTdp is thus very close to the capability of a full FTTP deployment. Cost savings compared to FTTP promise to be substantial — a possible 12 billion in savings for the Australian National Broadband Network — due to the use of existing copper pair lead-ins, thus avoiding civil engineering works for each individual fibre lead-in. Indeed, there is reason to expect that the initial cost of FTTdp deployment will be comparable to that of FTTN (Fibre to the Node). FTTdp has additional benefits of reduced copper maintenance and limited ongoing upgrade costs compared to FTTN. Significantly deeper fibre network penetration is potentially cost-neutral (or better) with FTTdp when compared to the FTTN baseline due to elimination of time-consuming activities involved with FTTN deployment. The reduced street impact of FTTdp is also important.